Acute Thrombolytic Therapy Combined with the Green Channel Can Reduce the Thrombolytic Time and Improve Neurological Function in Acute Stroke Patients. (27th June 2022) - Hong, Zhen; Zheng, Mingming; Li, Yan; Li, Shaoquan; Liu, Qingran; Xie, Songwang; Wang, Junyong; Wang, Jian; Liu, Yongchang
Abstract : Objective . To explore the effect of acute thrombolytic therapy combined with the green channel on the thrombolytic time and neurological function in acute stroke patients. Methods . A total of 100 acute stroke patients admitted to our hospital from August 2016 to August 2019 were recruited as the research cohort. In experimental group, 50 patients were administered green channel combined with acute thrombolytic therapy, while the patients in control group were administered general therapy. The thrombolytic times, the muscle strength grades, the FMA scores, the Barthel index levels, the NIHSS and SSS scores, the SAS and SDS scores, the arterial pressure and heart rates, the total effective rates, the incidences of postoperative adverse reactions, and the satisfaction levels were compared between the two groups. Results . The thrombolysis times in experimental group were shorter than those in control group. In experimental group, there were more patients with muscle strength grades 4 and 5 (P < 0.05 ), the FMA and Barthel index levels were higher, the NIHSS and SSS (P < 0.05 ) and the SAS and SDS scores were lower, the arterial pressure and heart rates were lower (P < 0.05 ), the incidence of postoperative adverse reactions was lower (P < 0.05 ), the total efficiency was higher (P < 0.05 ), and the satisfaction level was higher (P < 0.05 ). Conclusion . Acute thrombolytic therapy combined with the green channel can significantly reduce the thrombolytic time and improve the neurological function in acute stroke patients.